If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -34 + -2x = 11 + -7 Combine like terms: 11 + -7 = 4 -34 + -2x = 4 Solving -34 + -2x = 4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '34' to each side of the equation. -34 + 34 + -2x = 4 + 34 Combine like terms: -34 + 34 = 0 0 + -2x = 4 + 34 -2x = 4 + 34 Combine like terms: 4 + 34 = 38 -2x = 38 Divide each side by '-2'. x = -19 Simplifying x = -19
| 5/11=v/10 | | 5/11=v10 | | 87x-6x=8x+17 | | 87x-6x=8x | | y-(-4)=(-8/9)(x-8) | | 3(4a-7)=5 | | (-7u^2+8u+7)-(2u^2-9u-5)+(-7u^2+5u-7)= | | y-(-2)=(-3/4)(x-5) | | 2x-2=12-52 | | y-(-2)=(3/4)(x-5) | | 25b+20b^3= | | (2x)-(x-4)=5 | | f-(4/1/3)=10 | | 4x+8(x+1)+4=12-4x | | 2x-2(6-4x)=6(x-5)-26 | | f-(41/3)=10 | | 12k+131=3(4k+43) | | 0=-16x^2+40x+2 | | 10(x+2)-2x=2(4x+2)-8 | | 1.2k+2.3=-0.5+7 | | (5u^2+2)-(7u^2-4u+6)= | | 2[3-(6-5r)]-r=-12+3(2+3r) | | (2w^2+3)+(5w^2-4W-6)= | | U/3=12 | | x^2-6x-16/x^2+6x+8 | | (-7u^2+4u-3)+(5u^2+u+6)= | | M/6=8 | | (3t/4) | | (-5v^2+v-3)+(4v^2+6v+2)= | | 32-w=21 | | R-11=20 | | (-5v^2+4-3)+(4v^2+6v+2)= |